A novel microwave stimulus remote controlled anticancer drug release system based on Fe3O4@ZnO@mGd2O3:Eu@P(NIPAm-co-MAA) multifunctional nanocarriers1. Issue 34 (14th September 2015) - Qiu, Hongjin; Cui, Bin; Zhao, Weiwei; Chen, Ping; Peng, Hongxia; Wang, Yaoyu
<x xml:space="preserve">Abstract</x> A novel thermally responsive nanocarrier with mesoporous surfaces has been successfully prepared and developed for microwave stimulus remote controlled anticancer drug release.